Satellite Study of an Inland Monsoon Depression - KULSHRESTHA, S. M.; GUPTA, M. G. (MAUSAM, 1964)
This study describes and discusses an inland deep depression of the Indian south-west monsoon season with special reference to the associated cloud structure and rainfall pattern on 20 September 1962 and the consider which governed the recurvature which was most pronounced on that date. In addition to the conventional synoptic data, use has been made oft the observations obtained from TIROS VT satellite cameras. This is the first satellite study of an inland depression over India.